1971
DOI: 10.1029/ja076i007p01845
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal distribution of helium in the Earth's upper atmosphere

Abstract: The helium distribution in June 1969 was studied by using data from the mass spectrometer on Ogo 6 (perigee, 400 km; apogee, 1100 km). After normalizing for altitude effects by use of the Jacchia model atmosphere, the densities show an order of magnitude difference between the southern (winter) hemisphere and the northern (summer) hemisphere, with the maximum density occurring near −55° latitude. The exact location of the maximum varies between −40° and −70° geographic latitude and is apparently correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

1972
1972
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 4 publications
1
18
2
Order By: Relevance
“…Other ionic constituents such as He + and N § exist in the topside ionosphere, but they are usually minor constituents (Hoffman, 1967;Brinton et aI., 1969). The values of neutral hydrogen adopted by these authors are smaller by about an order or so than those obtained by Reber et al (1968) from direct measurements with satellite and by Brinton et al (1969) from measurements of ion composition in the F-region. Protons in the protonosphere are supplied by upward diffusion from the region of proton source by the reaction (18) during the day, and lost by downward diffusion to the region of proton sink by the reaction (18) in a reverse direction at night.…”
Section: Winter ~ Summercontrasting
confidence: 54%
“…Other ionic constituents such as He + and N § exist in the topside ionosphere, but they are usually minor constituents (Hoffman, 1967;Brinton et aI., 1969). The values of neutral hydrogen adopted by these authors are smaller by about an order or so than those obtained by Reber et al (1968) from direct measurements with satellite and by Brinton et al (1969) from measurements of ion composition in the F-region. Protons in the protonosphere are supplied by upward diffusion from the region of proton source by the reaction (18) during the day, and lost by downward diffusion to the region of proton sink by the reaction (18) in a reverse direction at night.…”
Section: Winter ~ Summercontrasting
confidence: 54%
“…Global properties in the distribution of composition and temperature, inferred from these measurements, were reported by Reber et al (1971), Taeusch et al (1971), , Carignan and Reber (1971), Hedin et al ( , 1973aHedin et al ( , 1973b), .…”
Section: Empirical Modelmentioning
confidence: 90%
“…New ratios in excess of an order of magnitude could then be obtained through this method as well. In addition to establishing a larger bulge ratio, Reber et al [55] noted a strong correlation of the maximum helium density with the location of the winter geomagnetic pole. This was interpreted as a sensitivity of the helium distribution to the thermospheric wind system.…”
Section: Introductionmentioning
confidence: 99%
“…Reber et al [55], using mass spectrometer measurements from the Ogo 6 satellite, showed an order-of-magnitude difference between the helium content in winter and summer hemispheres near 400-600 km altitude. This disagreement with previous results highlighted the limitations of the drag-inferred technique, specifically, reliance on the assumption of diffusive equilibrium to separate composition-induced mass density variations from those caused by temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation